2013
DOI: 10.1177/0969733013502802
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare professionals' perspectives on environmental sustainability

Abstract: The data highlight a disparity between personal and professional actions to address environmental sustainability. Given the constraints Australian healthcare professionals encounter, they are unlikely to shift to environmentally responsible practice without support from institutions and professional associations. Professional development is required to support this endeavour. The poor transference of pro-ecological behaviour from one setting to another is likely to have international implications for healthcar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
75
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(79 citation statements)
references
References 25 publications
1
75
0
3
Order By: Relevance
“…Despite of this, recent study has reported that nurses seldom expressed pro-environmental attitudes because they were afraid of conflict and stigmatization among their work communities. [12] This supports our findings of the need for strong environmental leadership and culture in hospital organizations.…”
Section: Scrutiny Of the Resultssupporting
confidence: 88%
See 3 more Smart Citations
“…Despite of this, recent study has reported that nurses seldom expressed pro-environmental attitudes because they were afraid of conflict and stigmatization among their work communities. [12] This supports our findings of the need for strong environmental leadership and culture in hospital organizations.…”
Section: Scrutiny Of the Resultssupporting
confidence: 88%
“…Administrators have a key role in leading initiatives because without their contribution hospital staff is less likely to act responsibly. [12,42] In addition to providing resources, it is an administrators' duty to clearly define roles in the organization to help people recognize their responsibilities and to stop them from passing them on to others. Administrators need to perceive sustainability as an inseparable basis of patient care and support people's endeavors with environmental managers leading the way.…”
Section: Scrutiny Of the Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…2) There was a strong sense of disconnect between local actions and global consequences with many healthcare professionals demonstrating a moral disengagement to the effects of AGW on developing countries (Grootjans and Newman, 2013). 3) Many physiological barriers to action were identified, including cognitive dissonance, denial, fatalism and bystander effect (Dunphy, 2014). 4) Social identity and social norms revealed a strong correlation between the desire to be socially accepted and the widespread silence on the topic, with fear of being ostracised or entering a politically emotive topic cited as a major barrier to engagement (Polivka, Chaudry, Mac Crawford, 2012).…”
Section: Resultsmentioning
confidence: 99%